Effect of mineral fillers on mechanical, thermal and morphological properties of kenaf recycled polyethylene wood plastic composite - Ros Azlinawati, Ramli; Nur Zuriati, Zakaria; Ummu Umaira, Abdul Rahman; Nur Basyirah, Ahmad Bakhtiar; Siti Noor Hidayah, Mustapha; Yuen, Mei Lian (Springer Berlin Heidelberg, 2018)
This contribution presents the effect of mineral filler on mechanical, thermal and morphological properties of wood recycled plastic composite (WrPC). WrPC was prepared using kenaf wood flour, recycled polyethylene (rPE) and maleic anhydride polyethylene (MAPE) with different types of mineral filler. All materials were premixed manually and fed into a twin screw extruder. The effect of graphite, mica and talc filler on impact strength, glass transition temperature (Tg), thermal degradation and morphological properties of WrPC was studied. The highest impact strength was achieved by graphite/WrPC at 6.99 kJ/m2 compared to WrPC at 4.29 kJ/m2. This is due to the presence of filler particles in WrPC leading to effective distribution of applied stress to overcome crack. DSC results indicated only one peak of Tg observed within 132–134 °C as a result of miscible blending. Decomposition of WrPC was slightly affected by incorporation of mineral fillers. The internal structure of WrPC with graphite/mica/talc fillers showed smooth morphology and better dispersion.